Implementation of Digital Marketing at Pancasetia College of Economics and Distance Learning, Banjarmasin, South Kalimantan - Rediyono (Indonesian Journal of Business Analytics, 2025)
Integrating digital marketing technologies like e-commerce, social media, and marketplaces is essential in higher education, especially in open and remote learning settings like Pancasetia College of Economics, Banjarmasin. These resources are essential for boosting student engagement and brand exposure. This study investigates how to strategically use digital marketing to get beyond obstacles that are typically connected to distant learning. Using thematic analysis to understand data gathered from many digital marketing platforms, a case study approach was employed to offer a thorough examination of digital marketing strategies at Pancasetia College of Economics, Banjarmasin. Search engine optimization, social media interaction, and video marketing were the three main facets of digital marketing implementation that the study highlighted. Inadequate internet connectivity, a lack of technological devices, a lack of expertise in content development, mismatched human resource qualifications, and excessive advertising expenses were among the main obstacles. This study provides information on how Pancasetia College of Economics in Banjarmasin may effectively use digital marketing to enhance accessibility and educational delivery.